Tahapan Desain dan Implementasi Model Machine Learning untuk Sistem Tertanam - Aminuddin Rizal (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2020)
machine learning and edge computing currently becomes popular technology used in any discipline. Flexibility and adapt to the problem are the main advantages of its technology. In this paper, we explain step-by-step way to make a lightweight machine learning model especially intended for embedded system application. We use open source machine learning tool called as Weka to design the model. Moreover, we performed a simple stress recognition experiment to make our own dataset for evaluation. We evaluate algorithm complexity and accuracy for different well-known classifier such as support vector machine, simple logistic and hoeffding tree.